Ethnomedicinal survey of plants used by local society in Poncokusumo district, Malang, East Java Province, Indonesia - Batoro, Jati; Siswanto, Dian (Asian Journal of Medical and Biological Research, 2017)
An ethnomedicinal survey was carried out in district Poncokusumo, Malang, East Java Province, Indonesia for documentation of important plants diversity and information from local society. The indigenous knowledge of traditional local societywas collected throught structural and open indept interview, direct observation and personal interviews during the research. To better acessesto the extractive activities and the utilization of the plant diversity by indigenous people. Plants with their correct nomenclature were arranged by vernacular name, family name, parts used, ethnomedicinal remedies and ethnomedical use. The determination and nomenclature of the listed plants were based on the Flora of Java.A Total of 181species plants (68 family) determinate of Tengger and Java people existing in the region. Family ethnomedicine plants that have large members includes Umbelliferae (3 species), Apocynaceae (4 species), Gramineae (6 species), Myrtaceae (7 species), Euphorbiaceae (8 species), Fabaceae (10 species), Zingiberaceae (10 species), Solanaceae (12 species) and Asteraceae (15 species).The number of plants used to treat more than 60 diseases. The treatment done by a medicine man or shaman from Tengger people by ritual treatment with called Suwuk Asian J. Med. Biol. Res. June 2017, 3(2): 158-167